Risk of addiction to social networks, self-esteem and self-control in high school students - Challco Huaytalla, Katherine Patricia (2019)
Objective: This research aimed to determine the relationship between the risk of addiction to social networks,self-esteem and self-control in students of 4th and 5th grade of high school of a public educational institutionin Metropolitan Lima. Methods: The sample consisted by 135 teenagers between 14 and 16 years old. Theinstruments used were the questionnaire of addiction to social networks (CARS), the self-esteem questionnaireof Coopersmith and the questionnaire of infant self-control and adolescents (CACIA). Results: In the resultswere found that there is a significant trade-off between the risk of addiction to social networks, self-esteem andself-control (r =-. 287; p =.001 and r =-. 288; p =. 001; respectively), That is to say, to lower self-esteem andself-control, greater will be the risk of addiction to social networks. Conclusions: The students show insecurity,isolation, low self-control over their conduct, the greater the risk of addiction to social networks.